PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN METODE BERMAIN PERAN DI SEKOLAH DASAR - Mayang Sari, Putri Dewi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the fact that learning in elementary school is often dominated by teacher and is still implementing a model of learning by learning to use the lecture method. Based on observations of the researchers on the 29th of april 2012 IPS students found the learning outcomes are low, to the researcher through action research is to try to improve student learning outcomes in learning dngan IPS using role play in class IV servants Elementary School District 1 New Taratak Tangjung Tower District Sijunjung. This type of research is a classroom action research, this study used a quantitative approach kualitatf and II cycles done collaboratively between researchers and teachers. The research data in the form of information on the outcome measures obtained from the observation and recording of every action in the social studies lesson about the importance of cooperatives to get to know people in the class IV welfare SDN 1 Taratak New District Tanjung district gadang Sijunjung, research subjects are teachers and students of Primary School IV terteliti The results showed that. Kata kunci: Hasil Belajar; pembelajaran IPS; Metode Bermain Peran